Folie a Deux: Shared Psychotic Disorder in a Medical Unit - Saumya Bhutani; Damir Huremovic (Case Reports in Psychiatry)
Introduction. A shared psychotic disorder is a system of delusions shared by two or more individuals. Shared psychotic disorders typically develop in pairs or groups with a close relationship who are socially isolated. The function and affect of those inflicted with shared psychotic disorders usually remain intact. For these reasons, a shared psychotic disorder is seldom identified, diagnosed, and treated. This case describes a shared psychotic disorder incidentally discovered in a medical unit. Case. The patient was a 47-year-old woman with no known past psychiatric history who had been medically admitted for gastroenteritis. On the day of discharge, a psychiatric consult was requested for “paranoia and bizarre behavior.” The patient was seen making statements that she needed security and the FBI to escort her as she left the hospital. Another person in the patient’s room was discovered to be the patient’s mother who had been staying with her in the hospital. Evaluation of the patient along with observation of her mother revealed that the two shared a complex system of delusions revealing a diagnosis of shared psychotic disorder. Discussion. A shared psychotic disorder is a unique psychiatric diagnosis. It may be even rarer to diagnose in the inpatient medical setting because multiple individuals from a shared system are typically not seen. In this case, the patient and her mother had multiple clinical characteristics of a shared psychotic disorder, including an enmeshed relationship and social isolation. The treatment for shared psychotic disorders involves separation of the individuals and pharmacotherapy with antipsychotics. This case also presented a unique ethical dilemma as the psychiatric team was called to evaluate a patient and found a patient and another individual to have symptoms. Conclusion. A shared psychotic disorder is important to consider on the differential when cases of psychosis with delusional systems are seen on medical floors.